Pengembangan Produk Genteng Tanah Liat dengan Integrasi QFD dan Value Engineering - Dyah Retno Purwatiningsih (Department Industrial Engineering, University of Muhammadiyah Malang, 2009)
One of the construction material product that's have highly required in constructing a house is house roof that Is roof tile. On of the producen that's produce its in big scale is in Wendit, a country side of Mangliawan. This product as people known is calls as Wendit roof tilet.Wendit produce its roof tile in low quality and cost of its that people prefer choose another roof tile product that have more level either in cost also quality. If this condition is continue without a will to improve its quality, distribution and much more according to satisfy customer desire roof tile producen of Wendit in country side of Mangliawan will close down. A side impact of its degradation is will decreasing the earnings of country side society of Mangliawan and also they social economics in matter the loost of their only life-way to gain a money will decreasing a level of life in social economic and also rise-up the number of unemployment. To answer this problematic this research covered: identification requirement of customer and translating into characteristic of performance by using QFD, developing alternative of design and also Value product for the alternative with Value Engineering. Attribute wanted by customer to tile product for example model, strong, refinement, do not be bars , cool, tile size is not undersize, is easy to attached, price. Satisfaction of customer to the attributes when measured with scale 5 is have good with score above 3. By attention tile industry of Wendit exist in Worse luck, hence technical action and attribute which must be done conducted by tile industry of Wendit is as according to priority shall be as follows: repair of model according to desire of market, adjustment of size measure, printer appliance or of desk have to is made from good materials, have to pay attention pressure at the time of printing, one who do printing process have to which is experienced to be, adapted for by size measure of pres concrete, tile materials have to really solid, process combustion with heat which enough.